Efficacy and safety of topical diclofenac/menthol gel for ankle sprain: A randomized, double-blind, placebo- and active-controlled trial. (April 2017) - Lai, Pamela M.; Collaku, Agron; Reed, Kenneth
Purpose: This study was performed to evaluate topical 1% diclofenac/3% menthol gel in treating ankle sprain. Design: In this randomized, double-blind, placebo-controlled trial, adolescents and adults with acute ankle sprain (N = 385) applied 4 g of gel containing 1% diclofenac/3% menthol (n = 117), 1% diclofenac (n = 112), 3% menthol (n = 77), or placebo (n = 75) four times daily. The primary outcome was the area under the curve of pain intensity (PI) on movement [0 (no pain) to 10 (extreme pain)] from 24 to 72 hours post-application (AUC1–3 days ). Secondary outcomes included pain relief (PR); PI; time to onset of PR, meaningful PR, cooling, and complete recovery; PI difference; sum of PI difference; total PR; reduction in ankle swelling; and the patient's global assessment of response to treatment. Results: There were no statistically significant differences in AUC1–3 between 1% diclofenac/3% menthol and placebo, diclofenac, or menthol gels and no meaningful advantages of 1% diclofenac/3% menthol for any secondary outcome. There was a higher incidence of skin and application-site events with 1% diclofenac/3% menthol than with placebo or 1% diclofenac. Conclusion: No significant improvement was observed with topical 1% diclofenac/3% menthol gel compared with placebo, 1% diclofenac, or 3% menthol gel in treating pain from ankle sprain. ClinicalTrials.Gov Identifier: NCT02100670